2017
DOI: 10.1016/j.jamcollsurg.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Older Patients with Grade III Cholecystitis and Cholecystostomy Tube Placement: A Propensity Score Analysis

Abstract: Background The Tokyo guidelines recommend initial cholecystostomy tube drainage, antibiotics, and delayed cholecystectomy in patients with grade III cholecystitis. Study Design We used Medicare data (1996–2010) to identify patients ≥66 years admitted with grade III acute cholecystitis. We evaluated adherence to the Tokyo guidelines and compared mortality, readmission, and complication rates with and without cholecystostomy tube placement in a propensity-matched (1:3) cohort of patients with grade III cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Such a consensus might have led to the increase in the proportion of AC patients aged ≥80 years who received percutaneous drainage over time in the current study. However, a recent report from the USA found that cholecystostomy tube placement was associated with higher mortality (30‐day HR 1.26, 90‐day HR 1.26, 2‐year HR 1.19) and higher readmission rates (30‐day HR 2.93, 90‐day HR 3.48, 2 years HR 3.08) in 565 elderly (aged ≥66 years) patients admitted with grade III AC than in 1689 propensity‐matched controls, suggesting a need for the re‐evaluation of PC in patients with grade III AC endorsed by TG13 . The acute cholecystitis in high risk surgical patients: percutaneous cholecystostomy versus laparoscopic cholecystectomy (CHOCOLATE) trial, which is the first randomized controlled trial evaluating the clinical value of PC against laparoscopic cholecystectomy in high‐risk AC patients, will hopefully clarify this point …”
Section: Discussionmentioning
confidence: 99%
“…Such a consensus might have led to the increase in the proportion of AC patients aged ≥80 years who received percutaneous drainage over time in the current study. However, a recent report from the USA found that cholecystostomy tube placement was associated with higher mortality (30‐day HR 1.26, 90‐day HR 1.26, 2‐year HR 1.19) and higher readmission rates (30‐day HR 2.93, 90‐day HR 3.48, 2 years HR 3.08) in 565 elderly (aged ≥66 years) patients admitted with grade III AC than in 1689 propensity‐matched controls, suggesting a need for the re‐evaluation of PC in patients with grade III AC endorsed by TG13 . The acute cholecystitis in high risk surgical patients: percutaneous cholecystostomy versus laparoscopic cholecystectomy (CHOCOLATE) trial, which is the first randomized controlled trial evaluating the clinical value of PC against laparoscopic cholecystectomy in high‐risk AC patients, will hopefully clarify this point …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have established the safety and efficacy of early CCY for patients with acute cholecystitis, including high-risk populations [6, 22, 23]. In addition, a recent propensity-matched analysis by Dimou et al [24] found that cholecystostomy tube placement was associated with increased mortality among elderly patients with Grade III cholecystitis. However, level I evidence comparing PC to CCY is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Mizrahi et al reported a significantly high rate of conversion to open surgery among patients who had undergone PTGBD before DLC and showed PTGBD to be an independent risk factor for this conversion (11). Dimou et al reported that tube placement in the gallbladder was associated with readmission with severe cholecystitis and mortality (12). We suppose that the PTGBD tube could cause bile leakage or a foreign body reaction, which would cause the changes characteristic of pericystic scarring.…”
Section: Discussionmentioning
confidence: 92%
“…Dimou et al . reported that tube placement in the gallbladder was associated with readmission with severe cholecystitis and mortality . We suppose that the PTGBD tube could cause bile leakage or a foreign body reaction, which would cause the changes characteristic of pericystic scarring.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation